KETAATAN HUKUM KEPALA DESA TERHADAP REGULASI DESA (Studi di Kecamatan Telaga Biru Kabupaten Gorontalo) - Salahudin Pakaya; Suslianto Suslianto (Maleo Law Journal, 2018)
In general the village head has to obey the existing village regulation, only sometimes they experienced pain points in the operational technical things, so to anticipate, village head consulting directly by confidently to local government especially on the dinas/technical agency dealing with the village government administration in this namely Dinas Community Empowerment Unit Gorontalo Regency. Consultation is effective steps to avoid the understanding of the regulation, so that protected also from kekelirua and error making policy decisions or in managing the village government program.The obedience of the village head to the rule because it was influenced by fears will be given the penalty for both the sanction administrative nature such as the reduction and/or temporary suspension of financial rights until the dismissal sanction with not distinguished from the office, especially if get the criminal sanction. In the sub-district Blue Pools there are already 2 (two) officials village heads who were dismissed because doing immoral, this has become the commitment of Gorontalo Regency Government that breach immoral is disgraceful act which is also a breach of the customs that are not necessarily done by the village head as the main figure indigenous peoples in the village as a citizen. Keyword : The obedience, Village Head, Village Rule